(untitled) (Journal on studies and research of academic knowledge, 2012)
This research consists on the evaluation of energy scenarios of the Electric System, where the final consumptions of the primary industry of the agricultural main products of the department of Itapúa-Paraguay are included, seeking this way to have a mark of reference initial to continue in the research in the diagnosis of industries of foods called more elaborated secondary industry of the agricultural sector. The considered products are the soya, the wheat, the rice and the sunflower. The current industrialization in this sector is of approximal 34%. The scenario analysis 100% of the primary industrialization in these areas shows an electric power demand of 51 MVA approximately (Megavoltsamperes) for a considered horizon of the year 2.021. This work can serve as base for the elaboration of an industrialization politics in the Department of Itapúa.